Characteristics of precipitating energetic electron fluxes relative to the plasmapause during geomagnetic storms. Issue 11 (4th November 2014) - Whittaker, Ian C.; Clilverd, Mark A.; Rodger, Craig J.
Abstract In this study we investigate the link between precipitating electrons from the Van Allen radiation belts and the dynamical plasmapause. We consider electron precipitation observations from the Polar Orbiting Environmental Satellite (POES) constellation during geomagnetic storms. Superposed epoch analysis is performed on precipitating electron observations for the 13 year period of 1999 to 2012 in two magnetic local time (MLT) sectors, morning and afternoon. We assume that the precipitation is due to wave‐particle interactions and our two MLT sectors focus on chorus (outside the plasmapause) and plasmaspheric hiss (inside the plasmapause) waves. We generate simple expressions based on the geomagnetic index, Dst, which reproduce the chorus‐driven observations for the >30 keV precipitating electron flux magnitudes. Additionally, we find expressions for the fitted spectral index to describe the flux variation with energy, allowing a full energy reproduction as a function of distance from the plasmapause. The hiss‐driven precipitating flux occurs inside the plasmapause but is independent of distance from the plasmapause. In the POES observations the hiss‐induced electron precipitation is only detectable above the instrument noise in the >300 keV and P6 (>800 keV) channels of the flux detection instrument. We have derived expressions for the storm time variation in flux inside the plasmapause using Dst as a proxy. The observations show that there is little evidence for >800 keV electron precipitation occurring outside of the plasmapause, in the MLT sectors studied.